What is the impact of a novel MED12 variant on syndromic conotruncal heart defects? Analysis of case report on two male sibs - Silvia Amodeo; Giuseppe Vitrano; Melania Guardino; Giuseppe Paci; Fulvio Corselli; Vincenzo Antona; Giuseppe Barrano; Monia Magliozzi; Antonio Novelli; Renato Venezia; Giovanni Corsello (BMC, 2020)
Abstract Background Syndromic congenital heart disease accounts for 30% of cases and can be determined by genetic, environmental or multifactorial causes. In many cases the etiology remains uncertain. Many known genes are responsible for specific morphopathogenetic mechanisms during the development of the heart whose alteration can determine specific phenotypes of cardiac malformations. Case presentation We report on two cases of association of conotruncal heart defect with facial dysmorphisms in sibs. In both cases the malformations' identification occurred by ultrasound in the prenatal period. It was followed by prenatal invasive diagnosis. The genetic analysis revealed no rearrangements in Array-CGH test, while gene panel sequencing identified a new hemizygous variant of uncertain significance (c.887G > A; p.Arg296Gln) in the MED12 gene, located on the X chromosome and inherited from the healthy mother. Conclusion No other reports about the involvement of MED12 gene in syndromic conotruncal heart defects are actually available from the literature and the international genomic databases. This novel variant is a likely pathogenic variant of uncertain significance and it could broaden the spectrum of genes involved in the development of congenital heart diseases and the phenotypic range of MED12-related disorders.